Germinability of Varieties of Bean (Phaseoulos Vulgaris L.) and Okra (Abelmoschus Esculentus L. Moench) Under Low Temperature Storage Condition: Bulk storage behavior of Bean and Okra - Indira Ariyarathna; Sarath Weerasena; Chalinda K. Beneragama (Indonesian Journal of Applied Research (IJAR), 2021)
Bean and okra are common vegetables cultivated in the most regions of Sri Lanka. The seeds of these crops are mainly stored in cold storage as bulk before releasing retail lots to sales outlets. Commercial growers and gardeners buy seeds in bulk or in packages at retail stores. Although certified seeds are frequently tested by the seed testing laboratories, they do not guarantee the maximum field emergence. Certified seed lots of two pole bean varieties, ‘Keppetipola Nil’ (KN) and ‘Bandarawela Green’ (BG) and two okra varities,’MI-5’ and ‘Haritha’ were stored in poly sack and polypropylene bags under controlled temperature (17±1 °C) and relative humidity (RH) (52-55%) over a two-year period. Bulk seeds of bean and okra varieties packed in polypropylene and poly sack bags depicted a high germination percentage throughout the storage period for two years. Seed quality parameters, seed germination, seed moisture, field emergence and vigour index significantly varied with the storage duration and declined in varieties. Significant differences in moisture, field emergence and vigour index were recognized as affected by the packing materials in all varieties except MI-5. Both Poly sack and polypropylene packing materials were found suitable to maintain viability at the minimum seed certification standards for two years of storage period. Poly sack was more appropriate than polypropylene to keep viability for more than 2 years of storage under low temperature and RH condition. These findings would help seed handlers including seed producers and seed sellers to store crop seeds between growing seasons in the tropical environment.